Relationship Parental Attention and Student’s Confidence - Widia Elfia Roza; Asmidir Ilyas (Universitas Negeri Padang, 2019)
Self-confidence is very important in the lives of students in school because there are no actions or behaviors that are not based on self-confidence. Attention from parents is one of the factors that influence a student to be confident, but in reality there are still many students who feel less confident. This study aims to examine the relationship between parental attention and the self-confidence of the SMAS students in the UNP Laboratory Development.This type of research is descriptive correlational. The research subjects were students of the XP and XI Laboratory Development Units in the total of 203 students. The instrument used in data collection was a questionnaire with Likert model scale answer choices. Analysis of the data used is descriptive analysis with percentage techniques and to see the relationship between the two variables used statistical analysis with the technique of Person Product Moment Correlation with the help of SPSS For Windows 20.0.The results of this study reveal (1) parental attention is in the high category, (2) student self-confidence is in the medium category, (3) there is a significant positive relationship between parental attention and student self-confidence. Based on the results of these studies, the researcher suggested that BK teachers develop and develop programs and provide services so that students were able to increase their confidence. In addition, BK teachers also need to collaborate with parents and school personnel in order to direct students to be more confident.